Viscoelastic-augmented trabeculectomy: A newer concept - Meghna Solanki; Ankur Kumar; Anubhav Upadhyay; Kishor Kumar (Indian Journal of Ophthalmology, 2017)
Purpose: Comparison of conventional trabeculectomy (CT) and viscoelastic-augmented trabeculectomy (VAT) in primary open-angle glaucoma. Methods: A total of 65 primary open-angle glaucoma cases were taken for each of the two groups, i.e., CT and VAT. Viscoelastic-augmented trabeculectomy constituted lamellar scleral flap, deep scleral flap, penetrating trabeculectomy, peripheral iridectomy, filling of the anterior chamber with viscoelastic (sodium hyaluronate) and balanced salt solution, movement of visco in bleb, and tight flap closure. Success criteria included intraocular pressure (IOP) <14 mmHg with no devastating complications. P < 0.05 was considered statistically significant. Results: Mean IOP was significantly lower after VAT compared to CT at 6 weeks, 12 weeks, and 6 months postoperatively. Target IOP was achieved in 60% cases in VAT group compared to 36.92% in CT group. Conclusion: VAT is effective in reducing IOP to the target level for advanced glaucoma with lower postoperative complications.